2016
DOI: 10.1089/ast.2015.1327
|View full text |Cite
|
Sign up to set email alerts
|

On Detecting Biospheres from Chemical Thermodynamic Disequilibrium in Planetary Atmospheres

Abstract: Atmospheric chemical disequilibrium has been proposed as a method for detecting extraterrestrial biospheres from exoplanet observations. Chemical disequilibrium is potentially a generalized biosignature since it makes no assumptions about particular biogenic gases or metabolisms. Here, we present the first rigorous calculations of the thermodynamic chemical disequilibrium in Solar System atmospheres, in which we quantify the available Gibbs energy: the Gibbs free energy of an observed atmosphere minus that of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 103 publications
6
119
0
Order By: Relevance
“…This result is consistent with Van Cleemput and Baert (), who concluded that NO2 in anoxic soils should decay, generally to N 2 . The situation on reducing prebiotic Earth is very different from the situation on oxidizing modern Earth, where in equilibrium NOX is thermodynamically favored (Krissansen‐Totton et al, ). Our thermochemical analysis confirms our kinetic analysis that previous work has overestimated prebiotic [ NOX], increasing our confidence in this conclusion.…”
Section: Thermochemical Equilibriummentioning
confidence: 99%
“…This result is consistent with Van Cleemput and Baert (), who concluded that NO2 in anoxic soils should decay, generally to N 2 . The situation on reducing prebiotic Earth is very different from the situation on oxidizing modern Earth, where in equilibrium NOX is thermodynamically favored (Krissansen‐Totton et al, ). Our thermochemical analysis confirms our kinetic analysis that previous work has overestimated prebiotic [ NOX], increasing our confidence in this conclusion.…”
Section: Thermochemical Equilibriummentioning
confidence: 99%
“…In situ biosignatures are physicochemical, geological, morphological, and mineralogical in nature (Summons et al , 2011). Remotely detectable biosignatures include gases in planetary atmospheres (Pilcher, 2004; Segura et al , 2005; Domagal-Goldman et al , 2011; O'Malley-James et al , 2014; Seager, 2014; Krissansen-Totton et al , 2016). Given an environmental analogy, it is conceivable that alien biospheres presenting similarities with ours may have generated and left traces we could recognize.…”
Section: Expanding the N Horizonmentioning
confidence: 99%
“…Historically, it was argued that the martian atmosphere is essentially at equilibrium and therefore Mars is unlikely to support life (Lovelock 1988;Lovelock 1975;Lovelock 1979). However, with modern observations, it is understood that Mars' atmosphere has the largest thermodynamic disequilibrium in the Solar System aside from Earth, with an available free energy of ~136 J per mole of atmosphere (Krissansen-Totton et al 2016). This free energy is predominantly attributable to the CO-O2 redox pair produced abiotically by the photolysis of CO2 and H2O in a thin, dry atmosphere.…”
Section: Introductionmentioning
confidence: 99%